Do You Have a Digital Wallet? A Study of E-Wallet during the COVID-19 Pandemic - Daisy Mui Hung Kee; Kah Huey Lai; Jia Ching Lee; Khang Jie Lee; Jia Long Lee; Idderena Yosanti; Dwi Nita Aryani (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
Following World Health Organization (WHO) recommendation, government officials are taking measures to facilitate non-contact payments that allow consumers to conduct contactless transactions, use cashless payment methods, and distance themselves physically from ATMs after the Corona Virus Disease 2019 (COVID-19) outbreak. COVID-19 is prevented from spreading through social distancing enabled by e-Wallets. Consequently, e-Wallets are becoming more popular to facilitate smoother, more efficient online transactions. We aim to investigate the key factors to use an e-Wallet since this COVID-19. The four factors included in the research are perceived risk, perceived ease of use, perceived convenience, and government support. Data from this study were collected through electronic questionnaires. The online survey received a total of 100 respondents who are e-Wallet users. Our findings disclosed that perceived risk, perceived ease of use, and perceived convenience are associated with intentions to use e-Wallets. The results offer useful insight into the field of e-Wallets.